2020
DOI: 10.1101/2020.08.12.248914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DeepCSO: a deep-learning network approach to predicting Cysteine S-sulphenylation sites

Abstract: Cysteine S-sulphenylation (CSO), as a novel post-translational modification (PTM), has emerged as a potential mechanism to regulate protein functions and affect signal networks. Because of its functional significance, several prediction approaches have been developed. Nevertheless, they are based on a limited dataset from Homo sapiens and there is a lack of prediction tools for the CSO sites of other species. Recently, this modification has been investigated at the proteomics scale for a few species and the nu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In this study, we compiled a benchmark data set of known Kcrot sites and evaluated the performance of different machine-learning approaches, including deep-learning algorithms. We found that the DLbased classifier CNNWE had the best performance compared with the traditional ML model and the LSTMWE model that showed superior to CNNWE for the prediction of cysteine sulphenylation sites, even for the limited training dataset [24]. It suggests that CNN and LSTM may have distinct characteristics that are feasible to extract different PTM features.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In this study, we compiled a benchmark data set of known Kcrot sites and evaluated the performance of different machine-learning approaches, including deep-learning algorithms. We found that the DLbased classifier CNNWE had the best performance compared with the traditional ML model and the LSTMWE model that showed superior to CNNWE for the prediction of cysteine sulphenylation sites, even for the limited training dataset [24]. It suggests that CNN and LSTM may have distinct characteristics that are feasible to extract different PTM features.…”
Section: Discussionmentioning
confidence: 90%
“…1) The input layer. Each peptide segment is converted into an integer vector with the NUM encoding approach, where each type of amino acid residues was mapped to a different integer [24].…”
Section: Deep Learning Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations